Piano Sonata no. 8 in C minor, op. 13, published by Bote & Bock - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::: (Berlin; Ed. Bote & G. Bock; Germany, 2022)
Early edition of the Piano Sonata no. 8 in C minor, op. 13, published in Berlin by Ed. Bote & G. Bock in 1838 or 1839.